Use of Rituximab in Autoimmune Hemolytic Anemia Associated with Non-Hodgkin Lymphomas - Claudio Fozza; Maurizio Longinotti (Advances in Hematology)
The association between non-Hodgkin lymphomas and autoimmune disorders is a well-known event. Also autoimmune hemolytic anemia (AHA), although much more frequent in patients with chronic lymphocytic leukemia (CLL), has been described in this group of patients. In recent years, among the more traditional therapeutic options, rituximab, an anti-CD20 monoclonal antibody, has shown interesting results in the treatment of primary AHA. Although this drug has been frequently used for AHA in patients with CLL, much less data are available on its use in NHL patients. However, considering that the main pathogenetic mechanism of AHA in course of lymphoproliferative disorders seems to be an antibody production directly or indirectly mediated by the neoplastic clone, this monoclonal antibody represents an ideal therapeutic approach. In this paper we will briefly describe some biological and clinical features of NHL-patients with AHA. We will then analyze some studies focusing on rituximab in primary AHA, finally reviewing the available literature on the use of this drug in NHL related AHA.